Fetal Endothelial and Mesenchymal Progenitors From the Human Term Placenta: Potency and Clinical Potential. (13th March 2015) - Shafiee, Abbas; Fisk, Nicholas M.; Hutmacher, Dietmar W.; Khosrotehrani, Kiarash; Patel, Jatin
Summary: : Since the isolation of fetal stem cell populations from perinatal tissues, such as umbilical cord blood and placenta, interest has been growing in understanding their greater plasticity compared with adult stem cells and exploring their potential in regenerative medicine. The phenomenon of fetal microchimerism (FMC) naturally occurring during pregnancy through the transfer of fetal stem/progenitor cells to maternal blood and tissues has been integral in developing this dogma. Specifically, microchimeric mesenchymal stem cells and endothelial progenitors of fetal origin have now demonstrated a capacity for tissue repair in the maternal host. However, the use of similar fetal stem cells in therapy has been significantly hampered by the availability of clinically relevant cell numbers and/or contamination with cells of maternal origin, particularly when using the chorionic and decidual placenta. In the present prospective review, we highlight the importance of FMC to the field of fetal stem cell biology and issues of maternal contamination from perinatal tissues and discuss specific isolation strategies to overcome these translational obstacles. Significance: Over the last decade, fetal stem cells from a variety of sources have been reported and have shown potential clinical applications. This study briefly reviews recent findings in the fetal stem cell arena, and particularly human term placenta as a robust cell source that harbors large quantities of both fetal and maternal stem cells of various types. It also appraises prospective isolation of large quantities of fetal endothelial progenitor cells and pure preparations of fetal or maternal mesenchymal stromal cells from the same placenta. Abstract : The importance of fetal microchimerism to the field of fetal stem cell biology and issues of maternal contamination from perinatal tissues is highlighted and specific isolation strategies to overcome these translational obstacles are discussed.